Soil Carbon Transitions Supporting Climate Change Mitigation - Kurniatun Hairiah (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2018)
Maintaining and where feasible restoring soil carbon stocks is part of all sustainable development strategies that have a chance of meeting the global commitment of the Paris Agreement to contain global warming within a 1.5oC limit. Active policies to incentivize increased soil carbon storage require understanding of the drivers of soil carbon decline, as well as the conditions under which soil management leads to an increase. Soil carbon transitions -- shifts from decline to increase of soil carbon stocks -- have been recorded as part of agricultural intensification. Organic inputs supporting soil carbon may primarily depend on roots, rather than aboveground inputs, and thus on the choice of crops, trees, and grasses that make up an agricultural land use system.